Impacts of Reforestation on Stabilization of Riverine Water Levels in South Korea - Jaehyun Yoon; Saang Joon Baak; Min Young Seo; Taejong Kim (KDI Journal of Economic Policy, 2022)
We investigate how reforestation contributed to stabilization of riverine water levels in South Korea. For the purpose, we estimate an equation capturing dynamic relationships among rainfall, upstream-area tree stock, and downstream water levels in three river systems of Hongcheon, Mangyeong, and Hyeongsan, using daily observations of precipitation and water levels for the period from 1985 to 2005. Simulation based on estimation results shows that increase in the tree stock in a river basin leads to a significantly suppressed peaking in riverine water levels in response to an abrupt and concentrated rain in the upstream area. For instance, an hour-long concentration of 100mm rain results in 0.7m rise in water level if the volume of growing stock is 1 million m3 , whereas the rise in water level stays below 0.27m with 5 million m3 in the growing-stock volume.
Keywords: Q51; Q54; Q56; Q57; 330; Reforestation; Forest Management; Ecosystem Services; Flood Control; Sustainability